Odpowiedź :
[tex]A)\\\\5( \sqrt{3}-4)+ \sqrt{3}(6+2 \sqrt{3})=5 \sqrt{3}-20+ 6\sqrt{3}+6=11\sqrt{3}-14\\\\B)\\\\2\sqrt{ 6}(2+5 \sqrt{6})-3(5-4 \sqrt{6})=4\sqrt{6}+60-15+12\sqrt{6}=16\sqrt{6}+45\\\\C)\\\\4 \sqrt{2}(5 \sqrt{2}-6)+3 \sqrt{2}(7-4 \sqrt{2})=40-24\sqrt{2}+21\sqrt{2}-24=16-3\sqrt{2}\\\\D)\\\\5(3+2^3 \sqrt{ 7})-2(3^3\sqrt{7} -4)=5(3+8\sqrt{ 7})-2(27\sqrt{7}-4)=15+40\sqrt{7} -54\sqrt{7}+8=\\\\=23-14\sqrt{7}[/tex]
[tex]jezeli\ w\ D) \ jest \sqrt[3]{7} \ to\ bedzie\ nastepujace\ rozwiazanie:\\\\D)\\\\5(3+2 \sqrt[3]{ 7})-2(3 \sqrt[3]{7} -4)= 15+10\sqrt[3]{7}-6\sqrt[3]{7}+8=4\sqrt[3]{7}+23[/tex]
Odpowiedź:
A) 5(√3-4)+√3(6+2√3)
5√3-20+6√3+2×3
11√3-14+6
11√3-14
B)2√6(2+5√6)-3(5-4√6)
4√6+10×6-15+12√6
16√6+60-15
16√6+45
C)4√2(5√2-6)+3√2(7-4√2)
20×2-24√2+21√2-12×2
40-3√2-24
16-3√2
D)5(3+2³√7)-2(3³√7-4)
15+10 3√7-6 3√7+8
23+4 3√7